Development of a Neuro-Linguistic Programming-Based Debriefing Guide for Supervisory Skills Training in a Garment Factory - Kartiko Adi Pramono; Iis Prasetyo; Yudan Hermawan (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study aims to develop a debriefing guide to enhance the effectiveness of Supervisory Skill Training for internal trainers in garment-based work environments. The primary challenges in developing the guide include an instructional work culture and the persistence of negative leadership myths that hinder workplace comfort. Additionally, limited understanding of experiential learning and neuro-linguistic programming (NLP) among internal trainers contributes to the suboptimal quality of debriefing during training sessions. This research employs a qualitative approach using the 4D model. Data were collected through focus group discussions (FGDs) and analyzed using source and theoretical triangulation techniques. The findings indicate that the developed debriefing guide successfully integrates experiential learning principles with NLP techniques into a competency-based structure. The validity of the guide was confirmed through expert input from academics, practitioners, and users. The guide is deemed feasible as a reflective tool to improve the quality of facilitation in supervisory-level leadership training.